Professional Trajectory of Engineers in the Maquiladora Electronics Industry: The Case of Sanyo Video Components - María Ruth Vargas Leyva (Universidad Autónoma de Baja California, 2000)
This is a study of the career trajectories of engineers in the company Sanyo Video Components. Three stages in the development of the professional career are recognized: initial career stage, mid-career and late stage career. Results indicate that the career's trajectory is internally determined by the area of career development and job hierarchy. In external mobility, there are limitations of individual and family type; those of an individual type are age and area of career development; those of a family type are civil state, spouse's occupation and the presence and number of children. The results of other studies are confirmed in relation to the engineers' practical training in the business, based on the initial career stage, the step from the technical dimension to the administrative, and the decrease in promotion potential which comes with age, as well as the professional conversion process of engineers who have various types of professional training.